“One Belt One Road” Initiative of China: Promotion of Bi/Multilateral Regional Cooperation in South Asia (Patan Prospective Journal, 2022)
The concept of “One Belt One Road” is initiated by People’s Republic of China which could be a foundational basis of development in the region. The ideas reflected in the presentations of an international seminar, entitled “Exploring Issues on Trans Himalayan Cooperation”, organized by Trans Himalayan Research Centre (THRC) of Faculty of Humanities and Social Sciences (FOHSS) at Tribhuvan University (TU) on 21 May 2016. Based on the presentations of scholars from Nepal, China and Korea this paper, based on the presentations of the seminar, further argues that the One Belt One Road initiative will not only be “Connecting the peoples along the One Belt One Road routes” but also promoting multilateral regional cooperation in future strengthening South Asian regional cooperation. It eventually promotes Bi/Multilateral Regional Cooperation in South Asia taking into consideration that connectivity is key that connects different regions within and outside nations. However, connectivity alone is not enough and there is necessary to develop corridor to contribute economic development of country. It is therefore necessary to promote various kinds of bi/multilateral regional cooperation for the development of Trans Himalaya region of South Asia.